2012
DOI: 10.1063/1.3668262
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of dc-biased ac-electrokinetic flow over symmetrical electrodes

Abstract: This paper presents a numerical study of DC-biased AC-electrokinetic (DC-biased ACEK) flow over a pair of symmetrical electrodes. The flow mechanism is based on a transverse conductivity gradient created through incipient Faradaic reactions occurring at the electrodes when a DC-bias is applied. The DC biased AC electric field acting on this gradient generates a fluid flow in the form of vortexes. To understand more in depth the DC-biased ACEK flow mechanism, a phenomenological model is developed to study the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Theoretical modeling of the frequency-dependent pumping was further developed [49] and used to simulate different aspects of the ACEO pumping [50,51]. Furthermore, the effect of several parameters and pumping configurations were investigated, such as studying the effect of channel height, electrochemical reactions, and non-linear surface capacitance of the Debye layer [52]; controlling the pumping direction by switching the voltage using an inclined electrode array [53,54], pumping of two different electrolytes simultaneously through microchannels [55], bubble-free pumping [56,57] as well as ACEO pumping using biased AC/DC signals [48,[58][59][60][61], pulse voltage waveforms [57], square pole-slit electrode arrays [62], and arrays of asymmetric ring electrode pairs in the cylindrical microchannels [63]. Also, the comparison between fluid velocity on arrays of identical electrodes with AC voltage and a traveling-wave potential demonstrated that traveling-wave potential resulted in a higher fluid velocity [64,65].…”
Section: Aceo Micropumpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical modeling of the frequency-dependent pumping was further developed [49] and used to simulate different aspects of the ACEO pumping [50,51]. Furthermore, the effect of several parameters and pumping configurations were investigated, such as studying the effect of channel height, electrochemical reactions, and non-linear surface capacitance of the Debye layer [52]; controlling the pumping direction by switching the voltage using an inclined electrode array [53,54], pumping of two different electrolytes simultaneously through microchannels [55], bubble-free pumping [56,57] as well as ACEO pumping using biased AC/DC signals [48,[58][59][60][61], pulse voltage waveforms [57], square pole-slit electrode arrays [62], and arrays of asymmetric ring electrode pairs in the cylindrical microchannels [63]. Also, the comparison between fluid velocity on arrays of identical electrodes with AC voltage and a traveling-wave potential demonstrated that traveling-wave potential resulted in a higher fluid velocity [64,65].…”
Section: Aceo Micropumpsmentioning
confidence: 99%
“…The ICEK micropumps introduced so far are categorized as ACEO micropumps where the fluid velocity in the range of 0.1-2.5 mm s −1 has been reported with applying DC electric signals [58,60]. Huang et al [69] used ACEO micropumps functioning under AC voltage to generate fluid velocity in microchannels as high as 1.3 mm s −1 .…”
Section: Iceo Micropumps Bazant and Squiresmentioning
confidence: 99%
“…W.Y. Ng et al investigated the mechanism of the flow and concluded that a conductivity gradient drives fluid flow [38,39]. Deionized (DI) water [37,40], a 10 −4 M solution of KCl (conductivity 1 mS m −1 ), and a CuSO 4 solution (conductivity 4 mS m −1 ) [38] were used as working fluids.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting temperature distribution surrounding the electrode changes the local conductivity and permittivity, causing electrothermal (ET) fluid flow. [10][11][12][13][14][15][16][17][18][19][20] ET fluid flow has been used previously for mixing particle suspensions. 15 Taking the advantage of manipulating the fluid by ET forces and the particles by DEP forces, the present study applies these techniques for developing micromixers and microconcentrators.…”
Section: Introductionmentioning
confidence: 99%